Practice-Driven Research on Enterprise Transformation Second Working Conference, PRET 2010, Delft, The Netherlands, November 11, 2010. Proceedings - Harmsen, Frank; Proper, Erik.; Schalkwijk, Frank; Barjis, Joseph; Overbeek, Sietse; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The PRET working conferences are set up as a one-day event in such a way that it attracts an audience from both industry and academia. PRET 2010 was a continuation of the PRET 2009 working conference, which was organized as the industrial track at the 2009 CAiSE conference. The PRET 2010 working conference was organized as part of theenterpriseengineering week, and was co-located with PoEM 2010 and TEAR 2010 in Delft. The statement that modern-day enterprises are in a constant state of ?ux is in 2010 even more true than it was in 2009. The markets are in a state of confusion and seem to have no direction at all, as they are swinging back and forth depending on often contradictory signals and economic forecasts. As a consequence, enterprises, be they private businesses, government departments or other organizations, are taking their measures. Restructuring, divesting, - proving performance and merging are among the usual transformationactivities thatenterprisesconducttoprovideanswerstotheever-challengingdemandsthat are put on them. In addition to the tricky economic situation, developments like globalization, rapid technologicaladvancement, aging and the changing mindset of customers contribute to a situation in which nothing is certain anymore and in which change is the only constant. PRET approaches these developments and the impact they have on ent- prises from a holistic enterprise engineering perspective.
Situational Transformation -- Design and Engineering for Situational Transformation -- Building Blocks for Enterprise Architecture Management Solutions -- Organizational and Design Engineering of the Operational and Support Components of an Organization: The Portuguese Air Force Case Study -- Portfolio, Program and Project Management -- Architecture-Based IT Portfolio Valuation -- Project Portfolio Management in Practice -- Systemic IT Project Management: A Rational Way to Manage Irrationalities in IT Projects? -- Enterprise Architecture to Align Business and IT -- On Supporting Collaborative Problem Solving in Enterprise Architecture Creation -- Dealing with IT Risk in Nine Major Dutch Organizations -- Lines in the Water.
Keywords: Business; Information technology; Business -- Data processing; Software engineering; Application software; Management information systems; Computer science; Business and Management; IT in Business; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Software Engineering; Management of Computing and Information Systems; Electronic books